Pediatric Cranio-spinal Axis Irradiation: Comparison of Radiation-induced Secondary Malignancy Estimations Based on Three Methods of Analysis for Three Different Treatment Modalities. (April 2015) - Myers, P. A.; Mavroidis, P.; Komisopoulos, G.; Papanikolaou, N.; Stathakis, S.
Pediatric cranio-spinal axis irradiation (CSI) is a valuable treatment for many central nervous system (CNS) diseases, but due to the life expectancies and quality of life expectations for children, the minimization of the risk for radiation-induced secondary malignancies must be a high priority. This study compared the estimated CSI-induced secondary malignancy risks of three radiation therapy modalities using three different models. Twenty-four ( n = 24) pediatric patients previously treated with CSI for tumors of the CNS were planned using three different treatment modalities: three-dimensional conformal radiation therapy (3D-CRT), volume modulated arc therapy (VMAT), and Tomotherapy. Each plan was designed to deliver 23.4 Gy (1.8 Gy/fraction) to the target which was defined as the entire brain and spinal column with a 0.7 cm expansion. The mean doses as well as the dose volume histograms (DVH) of specific organs were analyzed for secondary malignancy risk according to three different methods: the effective dose equivalent (EDE), the excess relative risk (ERR), and the linear quadratic (LQ) models. Using the EDE model, the average secondary risk was highest for the 3D-CRT plans (37.60%), compared to VMAT (28.05%) and Tomotherapy (27.90%). The ERR model showed similarly that the 3D-CRT plans had considerably higher risk (10.84%) than VMAT and Tomotherapy, which showed almost equal risks (7.05 and 7.07%, respectively). The LQ model requires organ-specific cell survival parameters, which for the lungs, heart, and breast relevant values were found and applied. The lung risk for secondary malignancy was found to be 1.00, 1.96, and 2.07% for 3D-CRT, VMAT, and Tomotherapy, respectively. The secondary cancer risk for breast was estimated to be 0.09, 0.21, and 0.27% and for heart it was 9.75, 6.02 and 6.29% for 3D-CRT, VMAT, and Tomotherapy, respectively. Based on three methods of secondary malignancy estimation, the 3D-CRT plans produced highest radiation-induced secondary malignancy risk, and the VMAT and Tomotherapy plans had nearly equal risk. Pediatric patients must be treated with reducing long term sequelae as a priority.